Evaluating CSR Compliance and Its Reputational Impact: A Longitudinal Case Study of PT Vale Indonesia (2015–2024) - Muntaha, Muntaha; Rismawati, Rismawati; Erniyati Caronge, Erniyati Caronge; Wagay, Javaid Ahmad (PT. EQUATOR SINAR AKADEMIA, 2025)
This study assesses the execution of Corporate Social Responsibility (CSR) at PT Vale Indonesia Tbk, emphasizing adherence to established policies and its influence on the company's reputation. Corporate Social Responsibility (CSR), designed to enhance societal and environmental value, is essential for fostering public trust and customer loyalty. The employed methodology is a descriptive technique utilizing secondary data gathered from annual reports, CSR documents, and literature reviews. The research findings reveal that PT Vale continuously executes CSR initiatives, despite a decline in the number of activities from 667 in 2015 to 82 in 2022. In 2022, the amount of CSR funds given out rose to USD 4.9 million. This shows that these programs are now more focused on quality than quantity. The company's reputation has gotten better, as shown by awards and public support, like the 2024 PROPER Emas. This report suggests that to make things more sustainable, we should make social impact projects better, use less energy, and move CSR programs online.